Melancholia and the search for the lost object in Farah’s Maps - A.E. Eruvbetine; Solomon Ombatsola Azumurana (Tydskrif vir Letterkunde, 2017)
Maps, given its intriguing narrative thrusts and multi-axial thematic concerns, is arguably the most studied or analysed of Nur- rudin Farah's nine prose fictions. The novel's title as well as its synopsis has naturally dictated the focus of critics on the Western Somalia Liberation Front's war efforts geared towards liberating the Ogaden from Ethiopian suzerainty and restoring it to Somalia. The nationalist fervour, the war it precipitates and its fallouts of a strife-ridden milieu have such a pervading presence in the novel that the personal experiences of the novel's two major characters, Askar and Misra, are quite often discussed as basic allegories of ethnic and nationalistic rivalries. This paper focuses on the personal experiences of Farah's two major characters. It contends that the private story of Askar and Misra is so compelling and central to the many issues broached in the novel that it deserves significant critical attention. Drawing upon Sigmund Freud's and Melanie Klein's concepts of melancholia, the paper explores how central the characters' haunting sense of melancholia is to the happenings in Farah's Maps.